Prevalence of Information Stored in Arrays of Magnetic Nanowires Against External Fields - Allende-Prieto, S (Elsevier B.V., 2018)
Arrays of magnetic nanowires in porous alumina can be used to store information inscribed on the system by orienting the magnetization of selected wires pointing in a desired direction, so symbols can be read as ferromagnetic sectors. However, this information is subject to aging and the stored information could be gradually lost. We investigate here two mechanisms proposed to improve the prevalence of the stored information: opposite ferromagnetic band at the center of the symbol and bi-segmented nanowires acting as two layers of nanowires storing the same information. Both mechanisms prove to increase resistance to the action of external magnetic fields for the case of Ni wires in a geometry compatible with actually grown nanowires. Advantages and disadvantages of these mechanisms are discussed. © 2017 Elsevier B.V.